Endovascular Device Choice and Tools for Recanalization of Medium Vessel Occlusions: Insights From the MeVO FRONTIERS International Survey - Kashani, Nima; Cimflova, Petra; Ospel, Johanna M.; Singh, Nishita; Almekhlafi, Mohammed A.; Rempel, Jeremy; Fiehler, Jens; Chen, Michael; Sakai, Nobuyuki; Agid, Ronit; Heran, Manraj; Kappelhof, Manon; et al. (Frontiers in Neurology, 2021)
Background: Endovascular treatment (EVT) for stroke due to medium vessel occlusion (MeVO) can be technically challenging. Devices and tools are rapidly evolving. We aimed to gain insight into preferences and global perspectives on usage of endovascular tools in treating MeVOs. Methods: We conducted an international survey with 7 scenarios of patients presenting A3, M2/3, M3, M3/4, or P2/3 occlusions. Respondents were asked for their preferred first-line endovascular approach, and whether they felt that the appropriate endovascular tools were available to them. Answers were analyzed by occlusion location and geographical region of practice, using multinomial/binary logistic regression. Results: A total of 263 neuro-interventionists provided 1836 responses. Physicians’ first-line preferences were evenly distributed among stent-retrievers, combined approaches, and aspiration only (33.2%, 29.8%, 26.8%, respectively). A3 occlusions were more often treated with stent-retrievers (RR 1.21,95%Cl:1.07-1.36), while intra-arterial thrombolysis was more often preferred in M3 (RR 2.47,95%CI:1.53-3.98) and M3/4 occlusions (RR 7.71,95%CI:4.16-14.28) compared to M2/3 occlusions. Respondents who thought appropriate tools are currently not available more often chose stent retrievers alone (RR 2.07;95%CI:1.01-4.24) or intra-arterial thrombolysis (RR 3.35,95%CI:1.26-8.42). Physicians who stated that they do not have access to optimal tools opted more often not to treat at all (RR 3.41,95%CI:1.11-10.49). Stent-retrievers alone were chosen more often and contact aspiration alone less often as first-line approach in Europe (RR 2.12,95%CI:1.38-3.24; and RR 0.49, 95%CI 0.34-0.70, respectively) compared to the United States & Canada. Conclusions: In EVT for MeVO strokes, neurointerventionalists choose a targeted vessel specific first-line approach depending on the occlusion location, region of practice, and availability of the appropriate tools.